Answer:
4/pi=w-6/pi
<u>4</u><u> </u><u> </u><u> </u>=<u> </u><u>w</u><u>-</u><u>6</u>
<u>Pi</u><u> </u><u> </u><u> </u><u> </u><u> </u><u>pi</u>
Cross mutiply
Pi(w-6)=4(pi)
Wpi - 6pi =4pi
Collect like terms
Wpi=4pi + 6pi
Wpi =10pi
<u>Divide</u><u> </u><u>both</u><u> </u><u>sides</u><u> </u><u>by</u><u> </u><u>pi</u>
<u>Wpi</u><u> </u>= <u>10pi</u>
Pi pi
W = 10
Square Root of 7
= 2.64575131106
F(x)=(-2/((x+y-2)^(1/2))-(x+y+2)^(1/2)
the only irrational part of this expression is the (x+y-2)^(1/2) in the denominator, so, to rationalize this, you multiply the numerator and denominator by the denominator, as well as the other parts of the expression
also, you must multiply the -sqrt(x+y+2) by sqrt(x+y-2)/sqrt(x+y-2) to form a common denominator
(-2)/(x+y-2)^(1/2)-(x+y+2)^(1/2)(x+y-2)^(1/2)/(x+y-2)^(1/2)
(common denominator)
(-2-(x^2+xy+2x+xy+y^2+2y-2x-2y-4))/(x+y-2)^(1/2)
(FOIL)
(-2-x^2-y^2-2xy+4)/(x+y-2)^(1/2)
(Distribute negative)
(-x^2-y^2-2xy+2)/(x+y-2)^(1/2)
(Simplify numerator)
(-x^2-y^2-2xy+2)(x+y-2)^(1/2)/(x+y-2)^(1/2)(x+y-2)^(1/2)
(Rationalize denominator by multiplying both top and bottom by sqrt)
(-x^2-y^2-2xy+2)((x+y-2)^(1/2))/(x+y-2)
(The function is now rational)
=(-x^2-y^2-2xy+2)(sqrt(x+y-2))/(x+y-2)
The asnwer would be 768 cm^3<span />